2015
DOI: 10.1515/hsz-2014-0287
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution of FTY720 and FTY720-phosphate in immune cells – another aspect of Fingolimod action relevant for therapeutic application

Abstract: FTY720 (Fingolimod; Gilenya ® ) is an immunemodulatory prodrug which, after intracellular phosphorylation by sphingosine kinase 2 (SphK2) and export, mimics effects of the endogenous lipid mediator sphingosine-1-phosphate. Fingolimod has been introduced to treat relapsing-remitting multiple sclerosis. However, little has been published about the immune cell membrane penetration and subcellular distribution of FTY720 and FTY720-P. Thus, we applied a newly established LC-MS/MS method to analyze the subcellular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…To analyze if FTY720 or FTY720‐P have additional intracellular targets besides the extracellular S1P receptors, we used SphK2 −/− splenocytes. FTY720 is predominantly phosphorylated to FTY720‐P by SphK2, which is prevented in SphK2 −/− splenocytes . As expected, SphK1 but not SphK2 mRNA expression was detectable by qRT‐PCR in SphK2 −/− splenocytes, confirming the complete knockout of the enzyme (Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…To analyze if FTY720 or FTY720‐P have additional intracellular targets besides the extracellular S1P receptors, we used SphK2 −/− splenocytes. FTY720 is predominantly phosphorylated to FTY720‐P by SphK2, which is prevented in SphK2 −/− splenocytes . As expected, SphK1 but not SphK2 mRNA expression was detectable by qRT‐PCR in SphK2 −/− splenocytes, confirming the complete knockout of the enzyme (Fig.…”
Section: Resultssupporting
confidence: 80%
“…These results indicate that the effect of FTY720 is conserved for IFN‐ γ and not dependent on the stimulus. Nonphosphorylated FTY720 will not reach high nanomolar concentrations in the blood of MS patients, but in a previous study we analyzed the subcellular distribution of FTY720 and FTY720‐P in immune cells of the spleen and showed that both substances dramatically accumulate in these splenocytes several 100‐fold . Thus to outline consequences of our data, the inhibition of IFN‐ γ by FTY720 could be beneficial but on the other hand bear additional risks.…”
Section: Discussionmentioning
confidence: 79%
“…The stimulatory effect of FTY720 on synaptobrevin was observed when the drug reaches micromolar range. Pertinently, a study of intracellular accumulation of FTY720 demonstrated that micromolar levels are easily achievable 50 . Using LC-MS mass-spectrometry method the authors demonstrated that the lipophilic FTY720 accumulated several hundredfold inside cells reaching micromolar concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Yagi et al have demonstrated that in guinea‐pig hearts, concentration of fingolimod was 7.5 times higher than in plasma, while that of fingolimod‐phosphate was six times higher in the heart, compared to plasma. Furthermore, Schröder et al have recently shown in mouse splenocytes that an extracellular concentration of fingolimod‐phosphate of 144 nmol/L corresponds to an intracellular concentration of 49.796 μmol/L, a dramatic 346‐fold elevation. Therefore, our choice to use intrapipette concentrations of fingolimod‐phosphate in the nanomolar range (100 and 500 nmol/L) to evaluate the calcium channel‐blocking effect of the drug in tsA cells appears fairly reasonable.…”
Section: Methodsmentioning
confidence: 99%